Pengembangan Kompetensi Inti Dalam Rangka Meningkatkan Kemampuan Industri Kecil Dan Menengah Di Minahasa Tenggara - Khayatun Nufus (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2012)
A thought that could be the philosophy is to start from the small. This study emphasize that develop the competitiveness between inter-governmental is began to develop regional competitiveness. The implications for the region is expected improved performance of public institutions and increased competitiveness in the macro level. At the micro level, the local government must create an environment of healthy competition among entrepreneurs in the region, and encourage the development of the company to be a reliable company and to develop a cluster of certain business activities. It is therefore necessary effort to exploit comparative advantage (input), which includes labor, natural resources, and strategic location, as well as the culture of excellence.